Effect of different combination of stabilisers on the physical properties of pink guava juice / Hanisah Hamzah - Hamzah, Hanisah (Faculty of Applied Sciences, 2008)
Separation is one of the major problems for fruit juices producers. Although this separation is a normal occurrence in fruit juices but consumers associate it with low in quality. The objective of this study is to find the best combination of stabilisers in order to minimise the separation in pink guava juice produced. Three types of stabiliser combination was tested, they are carboxymethyl cellulose with xanthan gum, carboxymethyl cellulose with arabic gum and carboxymethylcellulose with pectin and the ratio of 70:30 were used for all combinations. Physical analysis including total soluble solid value, viscosity, colour, cloudiness and particle size determination were carried out. Sensory evaluation was conducted for taste, aroma, colour, mouthfeel and overall acceptability attributes. From the result obtained, the physical analysis conducted showed that xanthan gum provides highest viscosity and total soluble solid, and low in cloudiness. While for arabic gum, the result obtained was almost similar to the control but with lowest particle size distribution which indicated greater particle uniformity. While pectin gave highest particle size distribution. Based on consumer acceptability, consumers cannot detect the presence of stabiliser added, therefore all different combination of stabilisers studied in this project can be used for stabilisation of pink guava juice.